ANALISIS KEPEMIMPINAN, KOMPENSASI TERHADAP KINERJA GURU DAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI SMA/SMK YADIKA TANJUNG DUREN JAKARTA - Edi Siregar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
This research aims to know the influence of leadership, compensation on performance through work discipline as an intervening variable. The object of this research is the SMA/SMK Yadika Tanjung Duren Jakarta with 85 of respondents. data analysis is the analysis of the path and processed with SPSS program Version 22. Sampling method using quota Sampling is by examining the census or the population. The results of this study showed that there was no direct influence leadership against the discipline of work, there is a direct positive influence compensation against a work discipline, and there is the influence of the leadership and work discipline against compensation, there is a direct influence on the discipline of work on performance of teachers, teachers, performance against the leadership and direct influence negative compensation on performance of teachers.